POTENSI, KENDALA DAN PELUANG PENGEMBANGAN AGRIBISNIS KELAPA RAKYAT DI KABUPATEN SARMI, PAPUA/Potentials, Constraints and Opportunities of Community Coconut Agribusiness Development In Sarmi District, Papua - Sri Wahyuni Manwan; Martina Sri Lestari; Ghalih Priyo Dominanto (Jurnal Penelitian dan Pengembangan Pertanian, 2022)
Sarmi Regency is a coconut producer with a productive plant area of 5,085 ha or 19.9% of the total coconut area in Papua Province covering an area of 25,585 ha in 2019. There was an increase in land area of 60.96% from the previous year, but this increase was not accompanied by a significant increase in productivity. The low productivity is caused mostly by old coconut plants, not using high yielding varieties of coconut and maintenance activity not using cultivation technology. Nowadays, coconut productivity in Sarmi Regency is only 0.22 tons/ha, under the national coconut productivity 1.1 tons/ha. This paper discusses the prospects, constraints, and opportunities for developing coconut farming in Sarmi Regency, Papua. The area of coconut plantations in Sarmi Regency, coconut trees are only 60.6% productive, of which the rest is immature plantations, damaged plants and new plants. The existence of a large area of land is an opportunity for the development of smallholder coconut plantations in Sarmi Regency, Papua. The use of quality seeds and proper cultivation management is a necessity in increasing coconut production and agribusiness. Constraints faced in coconut agribusiness are the low productivity of smallholder coconut, post-harvest is not optimal, and production has not been able to be absorbed by the local market. The income per farmer in one coconut harvest is Rp. 600,449,- copra income Rp. 900,766,- and the income from coconut oil production is Rp. 1,000,871,-. The results of the feasibility calculation analysis show that the potential of smallholder coconut farming products in Sarmi Regency has an R/C ratio > 1, 1.71 (coconuts), 1.06 (copra) and 1.03 (coconut oil). Coconut agribusiness development strategy, namely the support of infrastructure to support the development of smallholder coconut plantations; Innovation in seed technology, cultivation, harvest and postharvest management; Empowerment and development of farmers; development of marketing networks through institutional participation.Keywords: Coconut, agribusiness, development AbstrakKabupaten Sarmi termasuk penghasil kelapa dengan luas areal tanaman produktif 5.085 ha atau 19,9% dari total areal kelapa di Provinsi Papua seluas 25.585 ha pada tahun 2019. Terjadi peningkatan luas areal pertanaman kelapa 60,96% dari tahun sebelumnya, namun tidak disertai dengan peningkatan produktivitas yang signifikan. Rendahnya produktivitas kelapa karena sebagian besar sudah tua, tidak berasal dari bibit unggul, dan tidak menerapkan teknologi dalam perawatan tanaman. Hingga saat ini produktivitas kelapa di Kabupaten Sarmi hanya 0,22 t/ha, jauh lebih rendah dari produktivitas nasional yang mencapai 1,1 t/ha. Makalah ini membahas prospek, kendala, dan peluang pengembangan usahatani kelapa di Kabupaten Sarmi, Papua. Areal perkebunan kelapa yang produktif di daerah ini hanya 60,6%, sisanya tanaman belum menghasilkan, rusak, dan baru. Lahan yang masih luas menjadi peluang pengembangan perkebunan kelapa rakyat di Kabupaten Sarmi, Papua. Penggunaan bibit berkualitas dan pengelolaan budidaya yang tepat menjadi keniscayaan dalam meningkatkan produksi dan agribisnis kelapa. Kendala yang dihadapi dalam agribisnis kelapa ialah rendahnya produktivitas kelapa rakyat, pascapanen tidak optimal, dan produksi belum mampu diserap pasar setempat. Pendapatan petani dari sekali panen buah kelapa adalah Rp 600.449, pendapatan dari kopra Rp 900.766, dan pendapatan dari produk minyak kelapa Rp 1.000.871. Hasil analisis menunjukkan, produk usahatani kelapa rakyat di Kabupaten Sarmi mempunyai R/C ratio 1,71 dalam bentuk buah kelapa, 1,06 dalam bentuk kopra, dan 1,03 dalam bentuk minyak kelapa. Artinya, produk kelapa dalam bentuk buah yang layak. Pengembangan agribisnis kelapa memerlukan dukungan sarana prasarana pendukung, inovasi teknologi perbenihan, budidaya, pengelolaan panen dan pascapanen. Selain itu diperlukan pemberdayaan dan pembinaan petani serta pengembangan jejaring pemasaran melalui kelembagaan.Kata kunci: Kelapa, agribisnis, pengembangan